Social support as a mediator between anxiety and quality of sleep among Chinese parents of special children - Xu, Junda; Tang, Jiliang (Frontiers in Psychology, 2023)
Objective The psychological problems among Chinese parents of special children (mental retardation, limb disorder, hearing impairment, autism, cerebral palsy and other types) should be paid more attention. The aim of this study was to investigate the association between anxiety, social support, coping style and sleep quality among Chinese parents of special children during the early COVID-19 epidemic, so as to provide more help for the mental health of parents of special children scientifically and effectively. Method A total of 305 Chinese parents of special children were invited to accomplish four questionnaires. Anxiety was measured by the Self-Rating Anxiety Scale, social support was evaluated by the Perceived Social Support Scale, sleep quality was assessed by the Pittsburgh Sleep Quality Index, and coping style was measured by the Simplified Coping Style Questionnaire. Results This study revealed that anxiety was positively correlated with sleep quality (p < 0.01) and negatively correlated with social support (p < 0.01) and coping style (p < 0.01). Sleep quality was negatively correlated with social support (p < 0.01), but not significantly correlated with coping style (p > 0.05). Social support was positively correlated with coping style (p < 0.01). The study confirmed that social support had a partial mediating effect on the relationship between anxiety and sleep quality. Conclusion The anxiety of parents of special children not only directly affects sleep quality, but also indirectly affects sleep quality through social support. Social support can alleviate the impact of anxiety on sleep quality through the mediating role.